Distinctive features of Zaprionus indianus hemocyte differentiation and function revealed by transcriptomic analysis - Cinege, Gyöngyi; Magyar, Lilla B.; Kovács, Henrietta; Varga, Viktória; Bodai, László; Zsindely, Nóra; Nagy, Gábor; Hegedűs, Zoltán; Hultmark, Dan; Andó, István (Frontiers in Immunology, 2023)
Background: Insects have specialized cell types that participate in elimination of parasites, for instance the lamellocytes of the broadly studied species Drosophila melanogaster. Other drosophilids, such as Drosophila ananassae and the invasive Zaprionus indianus, have multinucleated giant hemocytes, a syncytium of blood cells that participate in the encapsulation of the eggs or larvae of parasitoid wasps. These cells can be formed by fusion of hemocytes in circulation or originate from the lymph gland. Their ultrastructure highly resembles that of the mammalian megakaryocytes.Methods: Morphological, protein expressional and functional features of blood cells were revealed by epifluorescent and confocal microscopy. The respective hemocyte subpopulations were identified by monoclonal antibodies in indirect immunofluorescence assays. FITC-labeled Escherichia coli bacteria were used in phagocytosis tests. Gene expression analysis was done following mRNA sequencing of blood cells.Results: D. ananassae and Z. indianus encapsulate foreign particles with the involvement of multinucleated giant hemocytes and mount a highly efficient immune response against parasitoid wasps. Morphological, protein expressional and functional assays of Z. indianus blood cells suggested that these cells could be derived from large plasmatocytes, a unique cell type developing specifically after parasitoid wasp infection. Transcriptome analysis of blood cells, isolated from naïve and wasp infected Z. indianus larvae revealed several differentially expressed genes involved in signal transduction, cell movements, encapsulation of foreign targets, energy production, and melanization suggesting their role in the anti-parasitoid response. A large number of genes that encode proteins associated with coagulation and wound healing, as phenoloxidase activity factor like proteins, fibrinogen-related proteins, lectins and proteins involved in differentiation and function of platelets were constitutively expressed. The remarkable ultrastructural similarities between giant hemocytes and mammalian megakaryocytes, platelets and giant cell-derived anucleated fragments at wound sites hints at the involvement of this cell subpopulation in wound healing processes, in addition to the participation in the encapsulation reaction.Our observations provide insights into the broad repertoire of blood cell functions required for efficient defense reactions to maintain the homeostasis of the organism. The analysis of the differentiation and function of multinucleated giant hemocytes gives an insight into the diversification of the immune mechanisms.